'The way to improve ART outcomes is to introduce more technologies in the laboratory'. Issue 3 (March 2022) - Gardner, David K.
Abstract: To address the proposition that 'the way to improve ART outcomes is through the introduction of more technologies in the laboratory', it is prudent to first define what is considered to be improved outcomes. Evidently, this equates to an increase in the live birth rate but it should also include parameters such as time to pregnancy, cumulative pregnancy per oocyte retrieval and health of the resultant child. Furthermore, being able to maintain clinical results week in, week out through quality management also contributes to the overall success of a clinic, and hence can be considered an improved outcome. With regards to these outcomes, it is offered that not only does the introduction of several new technologies (defined here as instrumentation, techniques and enhanced computer utilization and analysis) have the potential to improve outcomes, but also some of them have the capacity to facilitate automation and standardization in the ART laboratory. Although the automation of procedures can be perceived as a justifiable goal itself, in this contribution the emphasis is on how new technologies could help more patients become parents of healthy children in the shortest possible time.